2020
DOI: 10.1111/ocr.12411
|View full text |Cite
|
Sign up to set email alerts
|

Could medications and biologic factors affect post‐orthodontic tooth movement changes? A systematic review of animal studies

Abstract: Immediately after the removal of orthodontic appliances, the teeth might start to drift away from their corrected position in an attempt to reach a new equilibrium. Medications and biologic factors could potentially modulate these processes. The objective of the present systematic review is to systematically investigate and appraise the quality of the evidence regarding the effect of various medications and biologic factors on the rate of relapse following active tooth movement. Search without restrictions in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 84 publications
(272 reference statements)
0
10
0
Order By: Relevance
“…Other adjunctive procedures have also been reported that enhance the stability of the orthodontic result [ 66 ]. Among them, circumferential supracrestal fiberotomy and interproximal reduction are the more prevalent for the moment [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other adjunctive procedures have also been reported that enhance the stability of the orthodontic result [ 66 ]. Among them, circumferential supracrestal fiberotomy and interproximal reduction are the more prevalent for the moment [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…External root resorption (ERR) is a common and unfavorable iatrogenic consequence of orthodontic tooth movement, which results in irreversible loss of root dentin and cementum. Several factors are deemed involved in ERR induction, such as individual biological variation, age, sex, genetics, and orthodontic force amount and duration [ 67 , 68 ]. There is a lack of reliable evidence and guidance for clinicians on the effectiveness of interventions used to manage ERR [ 69 ].…”
Section: The Potential Utilization Of Stem Cell-based Innovations In ...mentioning
confidence: 99%
“…The traditional orthodontic treatment using FOAs may potentially lead to complications associated predominantly with periodontal structures. A wide range of FOA-related side effects was observed, ranging from gingivitis to periodontitis, fenestration, dehiscence of crestal alveolar bone, gingival recession, and “black triangles effects” [ 67 , 68 ]. Currently, evidence-based and approved treatment modalities include the surgical approach, guided tissue regeneration, bone augmentation, and the application of growth factors and bioactive molecules to induce a physiological process of regeneration if required [ 73 ].…”
Section: The Potential Utilization Of Stem Cell-based Innovations In ...mentioning
confidence: 99%
“…While many patients experience relapse, its detailed mechanism has not yet been elucidated [ 2 ]. Basic research using rats and mice has been conducted to clarify this mechanism [ 3 ].…”
Section: Introductionmentioning
confidence: 99%